Development of MOF-based heterostructures for photocatalytic hydrogen evolution. Issue 35 (25th August 2020) - Tang, Hong-Liang; Sun, Xiao-Jun; Zhang, Feng-Ming
Abstract : The schematic shows the types of MOF based heterojunction materials for photocatalytic hydrogen evolution, including metal nanoparticle/MOF, inorganic semiconductor/MOF, MOF/g-C3 N4 and MOF/COF heterostructures. Abstract : The construction of metal–organic framework (MOF) based heterostructures are a promising strategy to improve the photocatalytic hydrogen evolution activities of MOFs. For the intrinsic porosity, inorganic–organic hybrid nature and structural tunability of MOFs, a wide variety of MOF-based heterostructured photocatalysts with improved hydrogen evolution activities have been fabricated. In this frontier article, we present the latest advances in MOF-based heterostructures for photocatalytic hydrogen evolution. The opportunities and challenges related to MOF-based heterostructured photocatalysts are also presented.